Research on Torsional Fatigue Test Method of Electric Vehicle Differential based on Actual Driving Load - Xihong Zou; Jinxiao Li; Qiuyang Hu; Shuaijie Xi; Lingfeng Fu; Dongmei Yuan (Jixie chuandong)
Due to the high-frequency torque characteristics of electric vehicle motors，the impact load of their effect on the fatigue life of transmission systems such as reducers and differentials has been paid more and more attention by enterprises. According to the actual torsion load of electric vehicle differential， a torsion fatigue test system of electric vehicle differential based on hydraulic servo is designed. A wireless telemetry system is used to collect the axle shaft torque of electric vehicle in Dianjiang test site according to Pascal test specification. After preprocessing the collected axle shaft torque load spectrum and analyzing the characteristics in time-frequency domain， it is determined that the load waveform of torsional fatigue test is sine wave and the load frequency is 0.5 Hz. Through rainflow counting and extrapolation， the loading amplitude and frequency are determined，thus a torsional fatigue test method for differential of electric vehicles is established. Finally，an electric vehicle differential torsion fatigue test system is set up to verify the test method. The results show that the fatigue failure parts and forms of the differential are consistent with those of the real vehicle，and the established method is effective and feasible.